2000
DOI: 10.1073/pnas.97.1.240
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine hydrochloride blocks a critical step in the propagation of the prion-like determinant [ PSI + ] of Saccharomyces cerevisiae

Abstract: The cytoplasmic heritable determinant [PSI ؉ ] of the yeast Saccharomyces cerevisiae reflects the prion-like properties of the chromosome-encoded protein Sup35p. This protein is known to be an essential eukaryote polypeptide release factor, namely eRF3. In a [PSI ؉ ] background, the prion conformer of Sup35p forms large oligomers, which results in the intracellular depletion of functional release factor and hence inefficient translation termination. We have investigated the process by which the [ curing ͉ Sup3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
210
4
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(237 citation statements)
references
References 40 publications
22
210
4
1
Order By: Relevance
“…Because Gdn inactivates Hsp104 immediately, kinetics of [PSI ϩ ] curing after this inactivation can be monitored straightforwardly. When growing cells are exposed to Gdn there is a lag phase during which no curing occurs followed by a linear increase in the number of cured cells over time (25).These kinetic studies have supported the model that Hsp104 acts by breaking up prion polymers, thereby generating new prion ''seeds.'' During the lag phase that occurs after Hsp104 activity is inhibited, the prion polymers or seeds are thought to grow in size but, failing to replicate, become diluted among the increasing number of dividing cells.…”
supporting
confidence: 49%
“…Because Gdn inactivates Hsp104 immediately, kinetics of [PSI ϩ ] curing after this inactivation can be monitored straightforwardly. When growing cells are exposed to Gdn there is a lag phase during which no curing occurs followed by a linear increase in the number of cured cells over time (25).These kinetic studies have supported the model that Hsp104 acts by breaking up prion polymers, thereby generating new prion ''seeds.'' During the lag phase that occurs after Hsp104 activity is inhibited, the prion polymers or seeds are thought to grow in size but, failing to replicate, become diluted among the increasing number of dividing cells.…”
supporting
confidence: 49%
“…Second, strains with impaired Hsp104 or Hsp70 activity are defective in the generation of new propagons (Ness et al, 2002;Song et al, 2005), whereas NatA mutants sustain wild-type propagon levels (Supplemental Figure S6). Third, the steady-state size of SDS-resistant Sup35 aggregates increases in [PSI ϩ ] strains deficient in Hsp104, Hsp70, or Hsp70 cochaperones (Eaglestone et al, 2000;Wegrzyn et al, 2001;Cox et al, 2003;Kryndushkin et al, 2003;Jones et al, 2004;Song et al, 2005;Fan et al, 2007;Kryndushkin and Wickner, 2007;SatputeKrishnan et al, 2007;Sadlish et al, 2008), an observation that is completely opposed to our findings for NatA mutants ( Figure 5C). In addition to these factors, the ubiquitin-conjugating enzyme Ubc4 and the Hsp70 family members Ssb1 and Ssb2 are predicted or proven substrates for NatA (Huang et al, 1987;Polevoda et al, 1999), are modifiers of the [PSI ϩ ] prion cycle Allen et al, 2007), and have demonstrated synthetic interactions with NatA (Gautschi et al, 2003;Pan et al, 2006).…”
Section: Discussioncontrasting
confidence: 56%
“…In the presence of GdnHCl, propagon replication is inhibited, and the templates existing in a given cell are redistributed to daughter cells upon division. Under these conditions, [PSI ϩ ] cultures begin to switch to the [psi Ϫ ] state after a lag phase, the length of which is directly related to the number of propagons (Eaglestone et al, 2000). On treatment with GdnHCl, wild-type and NatA mutant [PSI ϩ ] strains were cured of the prion state after a similar lag time (Supplemental Figure S6), suggesting that the number of prion templates is not affected by NatA function.…”
Section: Sup35 Efficiently Joins Prion Complexes In the Absence Of Namentioning
confidence: 73%
See 1 more Smart Citation
“…In particular, the three best characterized S. cerevisiae prions, Sup35, Ure2 and Rnq1, all require normal expression levels of the chaperone Hsp104 in order to be propagated efficiently [13,77,78]. In the case of Sup35, inhibition of the ATPase activity of Hsp104 similarly interferes with prion propagation [79][80][81] and overexpression of Hsp104 also results in curing of the prion phenotype [77]. To account for these observations, it is proposed that Hsp104 is required to produce new seeds from existing prion aggregates; while [72]; and the mutants K127E or V271E when combined with point mutations in the N-terminus (see text) [73].…”
Section: Chaperonesmentioning
confidence: 99%